Electronic Food Vouchers: Evidence from an At-Scale Experiment in Indonesia - Banerjee, Abhijit; Hanna, Rema; Olken, Benjamin A.; Satriawan, Elan; Sumarto, Sudarno (American Economic Review, 2023)
We compare how in-kind food assistance and an electronic voucher-based program affect the delivery of aid in practice. The Government of Indonesia randomized across 105 districts the transition from in-kind rice to approximately equivalent electronic vouchers redeemable for rice and eggs at a network of private agents. Targeted households received 46 percent more assistance in voucher areas. For the bottom 15 percent of households at baseline, poverty fell 20 percent. Voucher recipients received higher-quality rice, and increased consumption of eggs. The results suggest moving from a manual in-kind to electronic voucher-based program reduced poverty through increased adherence to program design. (JEL H53, I18, I32, I38, O12)